DEFORMASI PEMBULUH DARAH AKIBAT PENGAPURAN PADA DINDING PEMBULUH - Kusumaningsih, Anjani
Blood vessel is a part of the circulatory system that transports blood to carries food substances, such as protein, fat, glucose, etc, throughout the body. Hardening of blood vessel is caused by the build up of fatty deposits in the vesicular walls. This condition narrows the vessel and reduces their elasticity, which leads to a reduction in blood flow through the vessel as a result of clogging. It certainly affects the deformation in the vesicular walls. In this final project, we study blood vessel deformations due to clogging in the vesicular walls. We focus on considering two cases; first, the clogging of blood vessel with discontinuous elasticity which means that the hardening process has occurred for longer time and second, the clogging of blood vessel with continuous elasticity. The results indicate that blood vessel deformation is influenced by the amount and the intensity of clogging to the vesicular walls which are described by the elasticity parameter.